Pengaruh Berbagai Komposisi Kompos Tea Terhadap Produksi Dan Kualitas Sawi (Brassica juncea L.) - Yeni Afrida; T. Sabrina; Fauzi Fauzi (Jurnal Agroekoteknologi, 2015)
The aim of this study was to determine the effect of compost tea application and composition enriched oil palm empty fruit bunches Azotobacter in increasing the production of mustard. This research used a non-factorial randomized block design with 11 treatment and 3 replication. A: control, without TKKS compost, without coconut water. B: 150 gr TKKS, without coconut waterand molases. C: 150 gr TKKS, 1500 ml coconut water and 3500 ml aquadest.D: 300 gr TKKS, 3000 ml coconut water and 2000 ml aquadest,. E: 450 gr TKKS, 4500 ml coconut water and 500 ml aquadest,. F: 150 gr TKKS, 1500 ml coconut water and 3500 ml aquadest, molases 2%. G: 300 gr TKKS, 3000 ml coconut water and 2000 ml aquadest, molases 2 %. H:450gr TKKS, 4500 ml air kelapa dan 500 ml aquadest, molases 2 %. I:150grTKKS, 1500 ml coconut water and 3500 ml aquadest, molases 4 %. J: 300 gr TKKS, 3000 ml coconut water and 2000 ml aquadest,molases 4 %. K: 450 gr TKKS, 4500 ml coconut water and 500 ml aquadest, molases 4 %. The next data is analyzed by ANOVA parameters and in the advanced test for real treatment using DMRT. The results of research showed that the composition of the compost with different doses provide no real influence to the high, leaf lenght and width of the leave of plantKeywords : Oil-Palm Empty Fruit Bunch Compost, compost tea, molasse